(3GdfUjMI aj EQTGO GdWdHIs
(3ChdgG (B:s
(3hHYO agPg ChQGb ENJUQJgG ef cJGH hbaJ Ydjg SeGg eDdag YeOI GdWdHI hCfG CRjO Ydjg ahGFO hPdc cdI ai COdI JYdje GdeJYde s
(3BNQgG (B:s
(3hGSJCKQJ Hg ai Yde GdZjH YfOc hROJ dg ahGFO LekG hBNQ OYhGfG Cf GdMeO ddg QH GdYGdejf GfJgi hcai hSdGe Ydi YHGOg GdPjf EUWai s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3?(B) s
Keywords: (3GdeLGejYs